Photocatalytic degradation of hydrocarbons present in water, using Fe (III) modified TiO2 - Velosa- Alfonso, Paula Catalina; Loaiza- Carreño, Andrés Felipe; Quiñones- Segura, Cesar Augusto (CT&F - Ciencia, Tecnología y Futuro, 2019)
ABSTRACT This research work focused on the degradation of total hydrocarbons in synthetic water mixtures and in samples obtained from the inflow of a skimmer (production water) by means of heterogeneous photocatalysis. Titanium dioxide (TiO2) was used, modified with iron oxide (III) as photocatalyst, supported on polymethyl methacrylate plates, arranged in two reactors with volumetric capacities of 15.0 mL and 1.0 L. The degradation process was studied using two analysis methods: Photometric detection and gravimetric partition. Degradation percentages of 91.2% and 98% were obtained in field samples and synthetic mixtures respectively, with 4 h times; this allows for assessment of this technique's impact on the treatment of produced water in the oil industry, seeking for an alternative to the methods for treating water contaminated with hydrocarbons.